2009
DOI: 10.2741/3417
|View full text |Cite
|
Sign up to set email alerts
|

TNF-alpha enhances engraftment of mesenchymal stem cells into infarcted myocardium

Abstract: TNF-alpha released from ischemic heart after acute MI increases the production of other cytokines such as interleukin-1 (IL-1), interleukin-6 (IL-6) and adhesion molecules such as intercellular adhesion molecule-1 (ICAM-1). Activation of nuclear factor kappa B (NF-kappa B) by TNF-alpha , up-regulates the expression of molecules which are involved in inflammation and cell adhesion. For these reasons, we assessed the extent that treatment of MSC with tumor necrosis factor (TNF)-alpha modifies the characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 19 publications
1
32
0
1
Order By: Relevance
“…MSCs can up-regulate both intracellular and membrane expression of CXCR4 after a short pretreatment with cytokines, gaining enhanced engraftment ability to the bone marrow of irradiated NOD/SCID mice, and transplantation of cytokines-treated MSCs results in faster hematological recovery [74]. Another recent study showed that TNF-α pretreatment before transplantation could increase MSC engraftment efficiency and improve recovery of cardiac function after cardiac infarction [81].…”
Section: Enhancing the Immunosuppression And Engraftment Of Mscs By Pmentioning
confidence: 99%
“…MSCs can up-regulate both intracellular and membrane expression of CXCR4 after a short pretreatment with cytokines, gaining enhanced engraftment ability to the bone marrow of irradiated NOD/SCID mice, and transplantation of cytokines-treated MSCs results in faster hematological recovery [74]. Another recent study showed that TNF-α pretreatment before transplantation could increase MSC engraftment efficiency and improve recovery of cardiac function after cardiac infarction [81].…”
Section: Enhancing the Immunosuppression And Engraftment Of Mscs By Pmentioning
confidence: 99%
“…This dual role is exemplified by the proinflammatory cytokine TNF-α. While sustained upregulation has a destructive role in many inflammatory conditions, TNF-α also acts as a growth factor for myelin-producing cells (114), differentiation factor for mesenchymal stem cells (115), and potential therapeutic in the infarcted myocardium (116) or bone fractures (117).…”
Section: Alarmins As Regenerative Therapymentioning
confidence: 99%
“…While most initial studies underlined a negative prognostic role of elevated levels of circulating TNF-a in the physiopathology of heart failure (HF) in AMI patients, other more recent studies have suggested that TNF-a might exert a beneficial role by increasing the recruitment of mesenchymal stem cells (MSC) [5,6]. Interestingly, one of the major transcriptional targets of TNF-a is osteoprotegerin (OPG), a soluble member of the TNF receptor superfamily [7,8].…”
Section: Introductionmentioning
confidence: 99%